The effects of online peer-facilitated learning and distributed pair programming on students’ learning - Tsai, Chia-Wen; Lin, Michael Yu-Ching; Cheng, Yih-Ping; Lee, Lan-Yu; Chyr, Wen-Li; Lin, Chih-Hsien; Lin, Jian-Wei; Tsai, Meng-Chuan (Computers and education, 2023)
The COVID-19 pandemic has forced universities and schools around the world to adopt online learning. Teachers may wonder if their students can attain satisfactory learning performance in an online learning environment without teachers' on-the-spot attention. In order to develop students' skills in programming, promote their enjoyment of learning and intention to learn to program, the researchers integrated two innovative teaching approaches, using online peer-facilitated learning and distributed pair programming, and investigated the effects of these on students' online learning performance. This study conducted an experiment that included 128 undergraduates from four class sections of Department of Finance. Thus, the experimental design in this research was a 2 (Peer-facilitated learning vs. non-peer-facilitated learning) × 2 (Distributed pair programming vs. non-distributed pair programming) factorial pretest/post-test design. The participants in this research mainly consisted of four classes of students from a non-computer or information department who took a compulsory course on programming design.’ Both quantitative and qualitative data were collected in this study. According to the results, the peer-facilitated learning group exhibited significantly better development of programming skills, enjoyment of learning, and intention to learn, than the non-peer-facilitated learning group. However, expected effects of enhancing the learning of the students in this study who received the distributed pair programming were not found. The design of online pedagogy can be a reference for online educators. The implications of applying online peer-facilitated learning and distributed pair programming to support students’ learning and the design of online programming courses are discussed. •Very few studies discussed effective online teaching methods.•This study provided an effective online teaching method for programming.•Peer-Facilitated Learning (PFL) and Distributed Pair Programming (DPP) was adopted.•Learners who received online PFL had better programming skills.•Learners who received online PFL had better enjoyment, and intention to learn.